Mr. Death: The Rise and Fall of Fred A. Leuchter, Jr. - Morris, Errol (United Kingdom : Independent Film Channel, 1999)
“Mr. Death” is a cinematic portrait of the life and career of the infamous American execution device designer and Holocaust denier, Fred A. Leuchter, Jr. Son of a prison guard, Leuchter found himself in the execution game when, as an electrical engineer, he offered his services to help fix the electric chair used in North Carolina. After his success in North Carolina, other states contacted him to help with their execution devices, and Leuchter helped devise lethal-injection devices, gas chambers, and gallows as well. On the basis of his qualifications, in 1988 Leuchter was commissioned by German-Canadian publisher Ernst Zundel to conduct the first thorough forensic examination of the alleged Nazi gas chambers at Auschwitz and Birkenau in Poland. Leuchter testified that the alleged facilities were not — and could not have been — used for mass extermination. What he viewed as his definitive achievement, his paper The Leuchter Report, ultimately led to his fall, as states wouldn't work with him, Jewish groups targeted him, and neo-Nazis sought him.
Soros Documentary Fund
Duration: 01:49:00
Soros Documentary Fund
Keywords: Documentary films